2019
DOI: 10.1002/cpt.1324
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated With Vincristine‐Induced Peripheral Neuropathy in Two Populations of Children With Acute Lymphoblastic Leukemia

Abstract: Vincristine is one of the core chemotherapy agents used in the treatment of pediatric acute lymphoblastic leukemia (ALL). However, one of the major toxicities resulting from vincristine exposure is vincristine‐induced peripheral neuropathy (VIPN). When VIPN results in significant morbidity, the vincristine dose may need to be reduced, thus potentially decreasing the effectiveness of treatment. To date, there are no robust biomarkers used clinically to determine which patients will be at risk for worse neuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 47 publications
(52 reference statements)
1
40
1
Order By: Relevance
“…ALL patient data collection. Children with newly diagnosed precursor B-cell ALL were recruited from four academic medical centers: Indiana University School of Medicine/Riley Hospital for Children, the University of Michigan Comprehensive Cancer Center/Mott Children's Hospital, Vanderbilt University Medical Center/ Monroe Carell Jr. Children's Hospital, and George Washington University/Children's National Medical Center 49 . Participants were between the ages of 1 and 18 at the time of diagnosis and received vincristine according to a Children's Oncology Group (COG) treatment trial for acute lymphoblastic leukemia.…”
Section: Methodsmentioning
confidence: 99%
“…ALL patient data collection. Children with newly diagnosed precursor B-cell ALL were recruited from four academic medical centers: Indiana University School of Medicine/Riley Hospital for Children, the University of Michigan Comprehensive Cancer Center/Mott Children's Hospital, Vanderbilt University Medical Center/ Monroe Carell Jr. Children's Hospital, and George Washington University/Children's National Medical Center 49 . Participants were between the ages of 1 and 18 at the time of diagnosis and received vincristine according to a Children's Oncology Group (COG) treatment trial for acute lymphoblastic leukemia.…”
Section: Methodsmentioning
confidence: 99%
“…No association was found by Zgheib et al (2018) between VIPN and CEP72 (rs924607), Ewing's tumor-associated antigen 1 (ETAA1) (rs17032980) and Melatonin Receptor 1B (MTNR1B) (rs12786200). Li et al (2019) investigated two independent cohorts and used a meta-analysis to assess the association between multiple SNPs and VIPN. One SNP, rs1045644 (encoding for protein cochlin, which is associated with progressive hearing loss and vestibular imbalance), showed a protective effect against neuropathy, while rs7963521 (gene involved in angiogenesis) was associated with a higher risk of VIPN.…”
Section: Pharmacodynamics Stability Of Microtubules and Neurotoxicitmentioning
confidence: 99%
“… Li et al. (2019) investigated two independent cohorts and used a meta-analysis to assess the association between multiple SNPs and VIPN.…”
Section: Role Of Pharmacogenetic Variations In Chemotherapeutic Relatmentioning
confidence: 99%
“…A recent GWAS study found no association between the CEP72 gene and VIPN [ 20 ]. This study was not included in our meta-analysis because genotyping data was not published.…”
Section: The Cep72 Gene Polymorphisms As Vipn Biommentioning
confidence: 99%